Prospects of use of Caltha palustris in soil plant-microbial eco-electrical biotechnology - I. B. Rusyn; V. V. Vakuliuk; O. V. Burian (Regulatory Mechanisms in Biosystems, 2019)
Soil plant-microbial biosystems are a promising sustainable technology, resulting in electricity as final product. Soil microbes convert organic products of plant photosynthesis and transfer electrons through an electron transport chain onto electrodes located in soil. This article presents a study of prospects for the generation of bioelectricity by a soil plant-microbial electro-biotechnological system with Caltha palustris L. (Ranunculaceae), a marshy winter-hardy plant that develops early in the spring and is widespread in the moderate climatic zone, in clay-peat medium and with introduction of Lumbricus terrestris L. (Lumbricidae). The experiment was carried out in the wetlands of the Ukrainian Polissya and the Carpathian mountains in situ, and on the balconies and terraces of buildings to assess the possibilities of using green energy sources located directly in buildings. The electrodes were placed stationary in the soil to measure the values of bioelectric potential and current strength. We monitored the bioelectricity indices in open circle and under load using external resistors, and calculated the current density and power density, normalized to the soil surface covered by plants and electrodes. The revealed high maximal values of the bioelectric potential, 1454.1 mV, and current, 11.2 mA, and high average bioelectricity values in optimal natural conditions in wetlands in situ make C. palustris a promising component of soil plant-microbial bio-electrotechnology. We analyzed the influence of temperature and precipitation on the functioning of the soil plant-microbial biosystem. The use of thickets of C. palustris in wetlands in situ, as a stable source of plant-microbial eco-electricity in the summer, is complicated by the fact that the plant sensitively reacts to long periods of high temperature and periods of drought, which is accompanied by decrease in the level of bioelectric parameters. The cultivation of the marsh plant C. palustris as a component of electro-biosystems is possible on terraces and balconies of buildings. The cultivation of C. palustris in clay-peat soil with electrode system for production of eco-electricity on shaded balconies and terraces of buildings requires optimal irrigation, lighting, and introduction of L. terrestris into the substrate, which increase the bioelectricity values of this biotechnology.